Processing and preserving foods - Baricevic, Thomas; Video Education Australasia (Australia : Classroom Video, 2008)
This fascinating program looks at why we preserve and process foods, how we do it in different cultures and the health considerations we need to take into account when we do it today. The preservation of food has been a life-saving practice in every human society since the dawn of time. Food, by its very nature, begins to spoil almost as soon as it is harvested so, to survive and thrive in ancient times, people had to learn to preserve the bounty to see them through lean times. In frozen climates, meat was kept in the ice. In tropical climates food was dried in the sun. In moderate climates salt and oil did the work. And this preservation allowed mankind to put down roots and create a society by remaining in one location. Each culture preserved their local food sources using the same basic methods of food preservation such as drying, freezing, fermenting, pickling and curing. But, within cultures, the preservation of food isn?t strictly for sustenance. There are also cultural aspects. All across the world there are many religious and celebratory occasions where the preservation of foods now has a social and customary meaning. The approach is now taken that we preserve food because we want to, rather than because we have to. This program includes an introduction to the workings of HACCP -- Container.
Presenter and narrator, Kathy Berketa.
DVD format.
Keywords: Food Preservation; Food Industry